Implementasi Metode Simple Additive Weighting Pada Aplikasi Rekomendasi Tempat Pengungsian Akibat Bencana Banjir - Angga Try Ramdany; Eko Budi Setiawan (ULTIMA InfoSys, 2019)
BBWS Cimanuk-Cisanggarung is a technical implementation unit at the Directorate General of Water Resources, Ministry of Pekerjaan Umum and Perumahan Rakyat which has the task of carrying out water resources management in the river area. As for the background of this study is the difficulty of river field officers to notify the announcement to the people who will be affected by the flood due to overflowing rivers, because the announcement is still a simple medium that is using sirens and hoaxes or electric poles. Geotagging technology and Fire Cloud Messaging Technology (FCM) is one of the ways to help field officers make public announcements through smartphone media, namely notifications that include river photos and locations. The difficulty of the people who are close to the Cimanuk-Cisanggarung watershed to get information about evacuation places before the flood occurs, because many people choose a place of refuge with their own choice. This is what makes the government more extra to provide assistance to unknown refugee camps. Google Maps technology can help people get to refugee camps recommended by the government. This research method consists of identifying problems, methods of data collection, system analysis, system design, system implementation, testing, and drawing conclusions. The results of the study show that river field staff and the community can be used as a notification of the river that will overflow and provide information on the place of refuge.